(untitled) (Fiep Bulletin - online, 2014)
The study examines the postural effects on the wellness and the performance of fourteen professional female water polo athletes. (Téczely T Á 2006) There are no written studies on water polo, probably because it is assumed that there is no pain because Archimedes’s formula opposes the force of gravity. Currently athletes carry out exercises to compensate and to avoid any eventual pain that then disappears when they are out of the water according to motor control and learning theory (Raiola 2012). The aim is to understand the phenomenon in professional athletes using a tridimensional analysis of the surface of the torso and the baropodometric platform. This consists in examining the “3D” surface of the torso of fourteen professional water polo athletes, participants in the Italian Championship in the A1 series, and the data of the baropodometric platform. This data highlights curves that will then be considered with regards to athletic performance and well-being. The data of performance and well-being of the athletes is collected by a trainer for each single athlete. The study was carried out at the specialized center COR POR A of Gricignano (CE ) with the following apparatus: “Formetric Spinometer”. This allows the morphological 3D image of the torso, with extreme accuracy (error below 0.2 mm), speed, and safety thanks to the radiation free equipment. The postural Formetric check-up supplies a series of indicators which together give a detailed evaluation of the subject’s posture. For each athlete a synthesis chart was elaborated, showing a 3D reconstruction of the surface of the torso and the individualization of specific postural parameters with the data collected by the trainers on the athlete’s performance and well-being. This data was elaborated using a statistic model of linear regression. The evaluation of the data shoes no existent correlation between cases with pseudo pathological curves and their state of well-being and performance. While athletes with a near perfect exam often complained about occasional pain. There is a paradox regarding affection, performance and pain; in some cases it is low, while in some cases, it is the opposite. The results of the Archimedes’s principle and the force of gravity probably produce physiological adjustments in water.